The effect of video podcasts on learning English proverbs by Iranian EFL learners - Nikbakht, Ahmadreza; Mazdayasna, Golnar (Frontiers in Education, 2023)
The question of whether podcasting affects the processes of teaching and learning English language has been extensively studied in recent years. However, there are a limited number of studies on whether video podcasts can affect learning English proverbs. The current study investigated the effectiveness of video podcasts in terms of learning English proverbs in a nonnative environment. The research team used video podcasts and proverbs together to link culture and technology in the current study. The participants of this study were 31 undergraduate students majoring in English Language and Literature at Yazd University who had enrolled in a course entitled `Listening and Speaking'. They were randomly divided into two groups namely control group and experimental group. A pre-test was given to both groups before the intervention sessions. The control group was taught based on the traditional approach, and the experimental group was taught based on video podcasting. Following five weeks of the intervention, all the students in the two groups were given a post-test. The results of the post-test revealed that the students in the experimental group performed much better in comparison to the students in the control group. Preliminary results of this study can increase non-native English language teachers' awareness of using technology in their classes with respect to teaching English proverbs. Also, immigrants who intend to learn English language and culture can benefit from the findings of this research.